Fuzzy-based voltage - Ching-Tzong Su
This paper presents a new approach using fuzzy set theory for voltage and reactive power control of power systems. The purpose is to find a solution which takes both voltage security enhancement and loss reduction into account for an electric power system. The approach translates violation level of buses voltage and controlling ability of controlling devices into fuzzy set notations using a linearized model. A feasible solution set which achieves voltage improvement is first attained using the max-min operation of fuzzy sets, the final solution which takes power loss reduction into account is then determined employing the min-operation on the feasible solution set previously obtained. A modified IEEE 30-bus test system is used to demonstrate the application of the proposed approach. Simulation results show that the approach is efficient, simple, and straightforward
Keywords: Buses voltage; Computer simulation; Control design; Control simulation; Fuzzy set theory; Fuzzy-based voltage/reactive power scheduling; Linearized model; Loss reduction; Max-min operation; Modified IEEE 30-bus test system; Power systems; Reactive power control; Voltage control; Voltage security improvement